Copepods (Crustacea, Maxillopoda) from shallow reservoirs - Castilho-Noll,Maria Stela Maioli (2012)
AIM: Among the planktonic microcrustaceans, copepods Cyclopoida and Calanoida are the most representative groups, being the largest biomass of the plankton community. The aim of this work is to catalogue and analyze the distribution of copepod species (Crustacea, Maxillopoda) in pelagic and littoral zones from small reservoirs in the northwest of the São Paulo State, in dry and rainy seasons (2007 and 2009). METHODS: Zooplankton samplings were carried out in littoral and pelagic zones of 13 small shallow reservoirs (mean depth: 2.6 m) using vertical hauls and plankton net (45 µm). Water physical and chemical parameters were also monitored with a multiparameter Horiba® U10. RESULTS: Eighteen species of copepods were identified, 13 Cyclopoida and 5 Calanoida. There was no statistical difference between the distributions of species from the littoral and pelagic zones and neither between dry and rainy seasons. Three species occurred exclusively in the littoral zone - Eucyclops elegans, Paracyclops chiltoni and Mesocyclops ogunnus. Tropocyclops prasinus and Thermocyclops decipiens were the most frequent species in the studied environments. CONCLUSION: Our data suggest that in shallow reservoirs copepods present a homogeneous distribution between the littoral and pelagic zones and Cyclopoida are more diverse than Calanoida. Shallow depths and eutrophic state may be regarded as limiting conditions for the development of Calanoida in these reservoirs.